On Memory-Block Traversal Problems in Model Checking Timed Systems - Larsson, Fredrik; Pettersson, Paul; Yi, Wang (BRICS Report Series, 2000)
A major problem in model-checking timed systems is the huge memory requirement. In this paper, we study the memory-block traversal problems of using standard operating systems in exploring the state-space of timed automata. We report a case study which demonstrates that deallocating memory blocks (i.e. memory-block traversal) using standard memory management routines is extremely time-consuming. The phenomenon is demonstrated in a number of experiments by installing the Uppaal tool on Windows95, SunOS 5 and Linux. It seems that the problem should be solved by implementing a memory manager for the model-checker, which is a troublesome task as it is involved in the underlining hardware and operating system. We present an alternative technique that allows the model-checker to control the memory-block traversal strategies of the operating systems without implementing an independent memory manager. The technique is implemented in the Uppaal model-checker. Our experiments demonstrate that it results in significant improvement on the performance of Uppaal. For example, it reduces the memory deallocation time in checking a start-up synchronisation protocol on Linux from 7 days to about 1 hour. We show that the technique can also be applied in speeding up re-traversals of explored state-space.